1994
DOI: 10.1007/bf00933001
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba-specific human T-cell clones isolated from healthy individuals

Abstract: T-cell responses to pathogenic free-living amoebae, Acanthamoeba sp., were analyzed in healthy Japanese individuals. Of 20 healthy subjects, 10 (50%) showed significant proliferative responses of peripheral blood mononuclear cells to the soluble amoebic antigens in vitro. The antigens used were not mitogenic, and no evidence of amoebic superantigens was available. We established human T-cell clones reactive to Acanthamoeba, all of which were CD3- and CD4-positive, CD8-negative, and TCR-alpha beta-positive. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…Few studies have been conducted to investigate the interactions of Acanthamoeba with T lymphocytes. Tanaka et al (439) examined T-cell responses to Acanthamoeba antigens in healthy human subjects. T-cell clones from these subjects were established and analyzed for biological and functional activities.…”
Section: Role Of the Immune System In Acanthamoeba Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have been conducted to investigate the interactions of Acanthamoeba with T lymphocytes. Tanaka et al (439) examined T-cell responses to Acanthamoeba antigens in healthy human subjects. T-cell clones from these subjects were established and analyzed for biological and functional activities.…”
Section: Role Of the Immune System In Acanthamoeba Infectionsmentioning
confidence: 99%
“…The T-cell clones were categorized as being Th1 cells involved in delayedtype hypersensitivity reactions in that they produced gamma interferon in response to amebic antigens. Based on their observations, Tanaka et al (439) suggested that the low incidence of symptomatic disease in humans might be due to acquired protective immunity induced by T-cell responses.…”
Section: Role Of the Immune System In Acanthamoeba Infectionsmentioning
confidence: 99%
“…Affected patients, including healthy individuals upto 90%, carry the Acanthamoeba-reactive antibodies of IgM, IgG, and IgA isotypes with no significant differences between males (86.2%) and females (89.2%), indicating that humans are regularly exposed to Acanthamoeba and become sensitized with the amoebic antigens (Chappell, et al, 2001, McClellan, et al, 2002, Schuster, 2002, Khan, 2005a, Brindley, et al, 2009, da Rocha-Azevedo, et al, 2009. It has been reported that T cells from healthy individuals can react to Acanthamoeba antigens obtained from CSF and antigen-specific T cell clones capable of producing IFN-also have been derived (Tanaka, et al, 1994). Likewise, peripheral blood mononuclear cells from rheumatoid arthritis patients shows proliferative responses to A. polyphaga (Shadidi, et al, 2001).…”
Section: Immune Responses To Acanthamoebamentioning
confidence: 99%
“…Tais estudos seriam de grande interesse em saúde pública, uma vez que foi mostrada recentemente a presença de Acanthamoeba em mais da metade das piscinas analisadas na Alemanha, assim como em quase 100% das amostras de solo da Turquia (87) , além da observação feita no Japão de que cerca de metade dos indivíduos examinados apresentou anticorpos contra essas amebas (124) .…”
Section: Os Gêneros De Avl Considerados Potencialmente Patogênicos Sãounclassified
“…Além disso, Acanthamoeba é o hospedeiro natural de diversas bactérias, como várias Chlamydiales (33) e, especialmente, Legionella pneumophila, causadora da doença dos legionários em humanos (101,106,126) , o que aumenta ainda mais sua importância tanto ecológica como em saúde pública. Além disso, Acanthamoeba é freqüentemente isolada do trato respiratório superior de indivíduos assintomáticos (55,124) , sugerindo que o contato entre essas amebas e seus hospedeiros potenciais é bastante intenso. …”
Section: Organismos Do Gênerounclassified